STRUCTURAL IMPURITY OF AL IN QUARTZ FROM PALEOZOIC GRANITOIDS IN THE BOLSHOY KAVKAZ (GREAT CAUCASUS) - Kurasova S.P.; Boyev A.G.; Gurbanov A.G.; Koshchug D.G.; Fedyushchenko S.V.; Chernukha F.P. (My University, 1997)
A study was made of structural impurities of Al in quartz. The aim of the study was to reveal and trace the interconnection between the concentration of structural impurities and the total micro-element composition of the quartz, and between the concentration of impurities and the geochemical characteristics of the granitoids themselves. The study was carried out on granitoids of Paleozoic age from the Great Caucasus, which had already been studied by other methods. For this study the rock and quartz samples were subjected to AAS, photometry, chemical analysis, XRF analysis and electron paramagnetic resonance (EPR). The factors determining the content of the structural impurity of Al were determined and other conclusions are presented.
Keywords: Paleozoic; Paleozoic; Палеозой